Rapid determination of furosemide by combined spot test/diffuse reflectance spectroscopy to detect doping in sport - Luiz, Vitor Hugo Marques [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Elsevier, 2013)
This paper describes the development and application of a simple, cheap, and clean method for the quantification of furosemide in urine samples from athletes, to detect doping, using a combined spot test/diffuse reflectance spectroscopy procedure. The method is based on the complexation reaction of furosemide (5-(aminosulfonyl)-4-chloro-2-((furanylmethyl)amino)benzoic acid, dissolved in ethanol, with FeCl3 and the surfactant dodecyltrimethylammonium bromide (DTAB) in aqueous solution, yielding a colored compound on the surface of a filter paper. The reagent concentrations were optimized using a chemometric experimental design. The reflectometric measurements of the complex formed were carried out at 477nm. The linear range obtained was 1.65-9.00×10-3molL-1 of furosemide (R=0.997), and the detection and quantification limits were 4.9×10-4 and 1.62×10-3molL-1, respectively. The proposed method was successfully applied in the analysis of furosemide in spiked urine, demonstrating that it is a reliable alternative method for the detection of furosemide doping in sport. © 2012 Elsevier B.V..
Keywords: Diffuse reflectance spectroscopy; Doping; Forensic analysis; Furosemide